O direito forjado nas grotas e chapadas: os processos de construções legislativas pelas geraizeiras e geraizeiros do Alto Rio Pardo-MG - Aldinei Sebastião Dias Leão (2021)
This work analyzes the social processes of the search for formal recognition of the Geraiza traditionalities in the Alto Rio Pardo region, as a strategy to recover parts of their territories, the chapadas or common lands - the general ones, properly speaking - expropriated by policies by the government's developmental policies The lease of generals to eucalyptus monoculture companies, not considering the common use of these high areas of the landscape by the gerazeiros, produced an effect called cornering, which, in a synthetic analysis, it tells about the impacts suffered by these local populations, whose dwelling floor is located in the grottos and paths – the lowlands. Sometimes, the drying up of the springs, the loss of freedom and the non-fulfillment of the promises of improvements in life, triggered a reactive process of these communities, which sought to articulate, among themselves and with external partners, in order to regain control integral part of their territories. In this process of articulation, as these communities seek to advance in the reconquest of the territory, reoccupying plateaus, especially from the 2000s onwards, the inexistence or insufficiency of regulatory frameworks in the national legal system, capable of responding to their interests, becomes evident. social groups, guaranteeing them the safeguard and protection of their peculiar ways of doing and living and relating to the environment. In this sense, the processes of collective construction of municipal legislation are presented as tools forged by the geraizeiros in the itinerary for the formalization of their traditionalities and protection of their territories and waters. This study presents an analysis of these experiences of legislative innovation, inaugurated regionally by the generaizeira community of Sobrado, and replicated by the communities of Baixa Grande and Moreira, shed light on the contribution of these collective subjects of law to the construction of a counter-hegemonic thought, contrasting with the globalizing monoculture project.